Child support systems and government budgets: thorny policy choices to recover costs. (8th December 2022) - Meyer, Daniel R; Skinner, Christine; Cook, Kay; Fletcher, Michael
Abstract: Australia, New Zealand, the UK, and the USA instituted child support agencies in the late 1900s and had some policies that resulted in having lowered governmental expenditures when child support was paid. Building on previous research comparing these four countries, this article examines the extent to which these countries currently use explicit cost recovery policies, implicit policies revealed in programme interactions, and fees. Using data from country informants on hypothetical families, we show the percentage of child support payments that are retained through these different tools. In addition to characterizing country approaches, we discuss advantages and disadvantages of different cost-recovery strategies.